What Should We Do to Prevent Zoonoses with Pandemic Potential? - Deckers, Jan (Journal of applied animal ethics research, 2023)
The majority of new infectious diseases that affect human beings are zoonoses. Zoonotic pressure is increasing for various reasons. These include: 1) the growth of the human population; 2) the growing concentration of human beings; 3) the growing mobility of the human population; 4) the rapid growth in the human usage of nonhuman animals; 5) the increasing intensification of the farm animal sector; 6) increasing ecological degradation, and 7) the lack of political will to address the previous six factors. These factors and the interplay between them create perfect storm conditions for the emergence of zoonoses with pandemic potential. What compounds the problem is a lack of moral theory on how to prevent zoonoses and associated pandemics. This article aims to address this gap by drawing on interdisciplinary work on zoonotic and pandemic prevention.